PERAN AUDIT INTERNAL SUMBER DAYA MANUSIA UNTUK PENILAIAN KINERJA KARYAWAN - Fauziah; Yuliastuti, Nunung (Universitas Pawyatan Daha, 2022)
Abstract The role of human resource internal audit in assessing the performance of Fesyenindo company employees is very important and is a series of processes and techniques where employees need assurance of the accuracy of performance information. Human Resources Audit is a comprehensive assessment of the Human Resources program. Employee Performance Assessment is the result obtained from employee activities in accordance with the work and performance standards that have been set. The results of human resource audits of employees that have been carried out show that the rules set by the company have been implemented properly. With the existence of an internal audit of human resources in the company can remind employee performance. However, there are still some weaknesses in evaluating employee performance that are still not in accordance with applicable regulations and must be corrected.